(Re)defining urban villages and their potential in sustaining local authenticity: A case study of Da Lat, Viet Nam - Khoa Anh Doan (PLoS ONE, 2026)
Urban villages have been theorised in three dominant ways: as ethnic enclaves in migration studies, as the UK Urban Village Concept, and as villages-in-the-city in the Global South. Whether these interpretations can coexist within a single urban context remains insufficiently examined. This study addresses this gap through Da Lat, Viet Nam, where rapid urbanisation and the state-led Green Urban Village pilot project have brought these models into direct interaction. The study adopts a multidisciplinary, multi-method approach combining historical and literature review, spatial mapping, expert-based Delphi assessment, topic modelling, and multi-criteria evaluation using the Analytic Hierarchy Process with optimisation techniques. A total of 74 villages were assessed across eight evaluation criteria using a context-sensitive scoring framework. Findings confirm the coexistence of ViCs, core attributes associated with ethnic enclaves, and a future-oriented Urban Village Concept. Most existing villages scored positively, demonstrating strong socio-cultural and spatial embeddedness, while the ecological dimension remains underdeveloped. The Green Urban Village pilot aligns with environmental objectives but shows weak contextual integration. A scenario-based integration with an adjacent village yields a more balanced performance across all criteria. The study empirically demonstrates the coexistence of hybrid urban village forms and analytically illustrates how a relational approach – here referred to as Green Urban Village 2.0 – could anchor sustainability-oriented planning within existing village structures. The findings contribute to urban village theory and offer context-sensitive insights for sustainable neighbourhood planning in Viet Nam and comparable settings.